2018
DOI: 10.26480/mjg.02.2018.33.38
|View full text |Cite
|
Sign up to set email alerts
|

Physical Impact of Sea Level Rise to the Coastal Zone Along the East Coast of Peninsular Malaysia

Abstract: Sea level rise around the world caused by global warming since decade and effects on coastal especially country below mean sea level and country island. The prediction of sea level rise by 2100 is over 3m. Sea level rise increases caused by melting ice and thermal expansion. The impact of sea level rise concentrated along the coastal area. This paper studied the impact of sea level rise to physical parameters along the East Coast of Peninsular Malaysia. Seven physical variables such as geomorphology, shoreline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 12 publications
0
15
1
1
Order By: Relevance
“…On the other hand, series from United Kingdom ( 12 ), Istanbul (Turkey) ( 16 ), Northeast of Brazil ( 17 ), Marches (Italy) ( 18 ), Northern and Southern Nigeria ( 19 ), Southern Nigeria ( 20 ), and India ( 21 ), reported AME as the most frequent OTs using 2017 WHOc. Interestingly, other studies with 2005 WHOc, which includes KCOT, reported AME as the most frequent OTs: Ibadan (Nigeria) ( 6 ), Sichuan (China) ( 7 ), Sri Lanka ( 9 ), Kayseri (Turkey) ( 22 ), and Malaysia ( 23 ).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…On the other hand, series from United Kingdom ( 12 ), Istanbul (Turkey) ( 16 ), Northeast of Brazil ( 17 ), Marches (Italy) ( 18 ), Northern and Southern Nigeria ( 19 ), Southern Nigeria ( 20 ), and India ( 21 ), reported AME as the most frequent OTs using 2017 WHOc. Interestingly, other studies with 2005 WHOc, which includes KCOT, reported AME as the most frequent OTs: Ibadan (Nigeria) ( 6 ), Sichuan (China) ( 7 ), Sri Lanka ( 9 ), Kayseri (Turkey) ( 22 ), and Malaysia ( 23 ).…”
Section: Discussionmentioning
confidence: 98%
“…In the present study, the ages of the patients ranged from one to eighty-three years. Most OTs occurred within the second and third decades, with a peak in the second decade in Uberlandia (Brazil) ( 10 ), Pernambuco (Brazil) ( 11 ), Japan ( 15 ), Northeastern Brazil ( 17 ), India ( 21 ), Malaysia ( 23 ), and Greece ( 24 ). Other series showed a peak in the third decade ( 7 - 9 , 19 , 20 , 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…Di bahagian pesisir dan lepas pantai pula banyak tersingkap batuan Formasi Mersing, batuan volkano dan sedikit granit yang berketahanan tinggi terhadap hakisan membentuk tanjung batu, tunggul laut, tebing jurang dan pulau baki. Hakisan laut terhadap satah lemah yang terdedah pula menghasilkan banyak gua laut dan gerbang laut (Mohd Fauzi et al, 2013;JKSPMG, 2018;Isfarita et al, 2018).…”
Section: Evolusi Landskap Daratanunclassified
“…IOP Publishing doi:10.1088/1755-1315/1103/1/012011 2 Studies on the impact of a sea level rise has been done around the world such as in Egypt [1], Bangladesh [4], USA [5], Malaysia [6], India [2] and Australia [3]. The researchers who studied the impact of a sea-level rise in physical aspects are [7] and [8] while others studied the socioeconomic impacts [9]. Littoral states will have to respond to increasing sea level.…”
Section: Introductionmentioning
confidence: 99%